Social and safety elements in green highway index - Mazlan, Ain Naadia (2013)
A Green Highway is an inspiration for the infrastructure to be environmentally responsible and sustainable in all aspect. It is expected to be eco friendly and significantly will reduce the emission of carbon dioxide and other green house gases. To achieve green highway standard, focus should now be on harmonizing highway needs with local ecological protection consideration. How to avoid subsequent environmental destruction and excessive resource consumption? How to incorporate sustainable development concepts into highway projects? The need for promoting sustainability and green highway construction requires an assessment system. Green highway rating provides an update current version of highway management practices. Nevertheless, the social and safety factor are often than not, been reduce significantly and in some cases is not being addresses critically. The aim of this study is to identify the adequacy and the appropriateness of social and safety element to be included in green highway criteria and therefore to be utilised in Malaysian Green Highway Index and its assessment. Data were obtained through comprehensive literature review, experts’ interviews and distribution of questionnaires. The outcomes from the interview were analysed qualitatively. Average Index Value analysis have also been utilised for the result of the questionnaire. The study resulted in 7 main criteria and 12 sub criteria have been accepted to be used for green highway index assessment.